The Routledge International Handbook of Postmodern Therapies - Beres, Laura | https://orcid.org/0000-0001-6926-0562; Baird, Stephanie | https://orcid.org/0000-0002-5979-2300; Sanders, Jane | https://orcid.org/0000-0002-9039-5805; Vito, Rosemary | https://orcid.org/0000-0002-9021-1973 (Taylor & Francis, 2026)
The Routledge International Handbook of Postmodern Therapies includes contributions by leading international experts to provide an invaluable resource and reference for therapy students, scholars, educators, and practitioners. Along with discussing key postmodern approaches, including collaborative-dialogic, narrative, solution focused, and open dialogue, the handbook features advances in theory, research, and applications of postmodern practice. It covers both critical perspectives and methodologies, such as narrative, poststructuralist, performative, and postqualitative. Considerations of issues of diversity, power, and privilege are infused throughout the handbook. This handbook is essential for practitioners and students interested in teaching, using, and researching postmodern practice, including counselors, clinical psychologists, family therapists, psychotherapists, and social workers. Chapter 28 and Chapter 38 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial 4.0 license (CC-BY-NC).